The political economy of sovereign debt crises: The current state of the debate on debt restructuring mechanisms - Fernández Alonso, José (2018)
The goal of this research is to analyze the state of the contemporary debate on the mechanisms for sovereign debt restructuring. The article begins by unraveling the main guidelines supported by the proposals with the greatest political and economic impact since the opening of the debate, focusing specially on the developments reported in the following years. It also identifies the promoters of each one of them and the arguments that they putforward –and they still use today– regarding the problems that determine all the processes of sovereign debt restructuring. Finally, the work culminates with some closing considerations.